Combined Intravenous and Oral Calcimimetic Therapy for Secondary Hyperparathyroidism in Hemodialysis Patients Ineligible or Unwilling to Undergo Parathyroidectomy - Affan Tahir Bhatti, Khurram Danial, Allah Bux Mushtaq, Samiullah, Momin Khan, Muhammad Basharat Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Secondary hyperparathyroidism (SHPT) is a common and serious complication in chronic kidney disease patients on hemodialysis. For patients ineligible or unwilling to undergo parathyroidectomy, pharmacologic therapy with calcimimetics offers a non-surgical alternative. Objective: To evaluate the effectiveness and safety of combining intravenous (IV) and oral calcimimetic therapy in managing SHPT in hemodialysis patients who are either ineligible or unwilling to undergo parathyroidectomy. Methodology: This prospective study was conducted at Lahore general hospital during June 2021 to May 2022 and included 110 adult hemodialysis patients with uncontrolled SHPT. Patients were treated with a combination of IV etelcalcetide and oral cinacalcet for 24 weeks. Serum intact parathyroid hormone (iPTH), calcium, and phosphate levels were monitored at baseline, 12 weeks, and 24 weeks. Results: Combined therapy significantly reduced mean iPTH levels from 980 ± 220 pg/mL at baseline to 480 ± 180 pg/mL at 24 weeks (p < 0.001). Serum calcium decreased from 9.4 ± 0.6 to 8.8 ± 0.5 mg/dL (p = 0.01), and phosphate levels declined modestly. 68% of patients achieved >30% reduction in iPTH. Gastrointestinal side effects occurred in 14%, mostly mild; hypocalcemia was reported in 9%. Conclusion: Combined IV and oral calcimimetic therapy is effective in reducing iPTH levels and controlling biochemical parameters in SHPT patients on hemodialysis who cannot undergo parathyroidectomy. The regimen is well tolerated and provides a viable non-surgical management option. Keywords: SHPT, hemodialysis, calcimimetics, etelcalcetide, cinacalcet